Conflict Resolution Management in Papua: A Historical and National Integration Perspective - Sudarsono, Djayeng Tirto; Setiawan, Bayu (Dinasti Research, 2025)
The resolution of the conflict in Papua not only requires a security approach but also necessitates a holistic treatment involving social, economic, and political aspects. A profound understanding of the root issues and active participation from all involved parties are key to formulating sustainable solutions. Through this approach, it is hoped that Indonesia can achieve a resolution to the conflict in Papua that is not only tactical but also provides a strong foundation for the ongoing peace and prosperity of all Indonesian citizens, including our brothers and sisters in Papua. Strategic and conceptual thinking from the perspectives of history and national integration are integral to efforts aimed at resolving conflicts based on separatism and terrorism in Papua through a multidisciplinary approach. From the viewpoint of history and national integration, innovative approaches and more effective solutions can be identified to safeguard national security. Thus, it can serve as a basis for designing a conflict resolution model that considers the historical context and national integration in the Papua context. Research findings indicate that this model should ideally encompass diplomatic strategies, active participation of local communities, and sustainable development approaches. Looking ahead, this research is expected to stimulate further studies to generate more profound strategic thoughts, enrich insights, and make significant contributions to addressing the complexity of conflicts in Papua in order to maintain national security.